Real-world outcomes of immune checkpoint inhibitors as second-line therapy for extensive-stage small-cell lung cancer: a multicenter retrospective analysis - Zhang, Jiao; Guo, Jia-xing; Li, Ping; Jin, Xiao-ye; Wang, Yan; Zhao, Lu-jun (Frontiers in Immunology, 2025)
BackgroundThere is limited evidence concerning real-world efficacy of second-line (2L) treatment with immune checkpoint inhibitors (ICIs) in extensive-stage small-cell lung cancer (ES-SCLC). In this study, we evaluated the efficacy of 2L-ICIs therapy in patients with ES-SCLC.MethodsIn this retrospective study, we included patients with ES-SCLC who experienced disease progression following first-line (1L) therapy and received 2L treatment between March 2019 and December 2023. The primary endpoint of this study was progression-free survival (PFS), and the secondary endpoints included safety, the objective response rate (ORR), the disease control rate (DCR), and overall survival (OS). Survival analyses were conducted using Kaplan-Meier curves. One-to-one propensity score matching (PSM) was used to reduce confounding. Univariate and multivariate Cox regression analyses were conducted to identify factors associated with PFS and OS.ResultsWe included 496 patients in this study; among them, 200 patients were in the 2L-ICIs group and 296 patients were in the 2L-non-ICIs group. The 2L-ICIs group demonstrated significantly longer PFS than the 2L-non-ICIs group (median PFS: 4.13 vs. 2.70 months; p < 0.001), and this benefit persisted after PSM (median PFS: 4.14 vs. 2.84 months; p < 0.001). The 2L-ICIs group also had a significantly higher ORR (ORR: 29.5% vs. 10.1%; p < 0.001) and DCR (DCR: 67.0% vs. 51.7%; p < 0.001). Treatment-related adverse events were comparable between the groups, with only one grade 3 rash reported in the 2L-ICIs group. Multivariate Cox regression identified liver metastases, the number of metastatic lesions, and the 1L-PFS as independent predictive factors for PFS.ConclusionIn this study, 2L-ICIs demonstrate significant clinical benefits with acceptable toxicity in ES-SCLC patients who progressed after 1L therapy, supporting their use as a clinically actionable option.